Effects of 1-methylcyclopropene on postharvest quality of white- and yellow-flesh loquat (Eriobotrya japonica Lindl.) fruit. (12th September 2014) - Liguori, Giorgia; Farina, Vittorio; Sortino, Giuseppe; Mazzaglia, Agata; Inglese, Paolo
Abstract : Introduction . The effects of 1-methylcyclopropene (1-MCP) were evaluated on white-flesh cv. Claudia and yellow-flesh cv. Nespolone di Trabia loquat fruit.Materials and methods . Application of 1-MCP [(0.5 to 1) µL×L–1 for 20 h)] was monitored at 20 °C (7 days) and 0 °C (7 days at 0 °C and then 7 days at 20 °C).Results . Treatments with 1-MCP slowed fruit softening, depending on the concentration. Softening inhibition was greatest in fruit treated and held at 20 °C. The optimum concentration for softening inhibition at 20 °C was 1 µL×L–1 of 1-MCP, while 0.5 µL×L–1 of 1-MCP was more effective at 0 °C.Conclusion . Treatments with 1-MCP inhibited titratable acidity loss in both cultivars. 1-MCP extends the shelf life of rapidly softening, perishable fruits such as loquat fruit.